Предмет: Математика,
автор: olgaverminko
c) -y(3y + 4); f) -3y(y + 7); i) -2y(-y-4).
Ответы
Автор ответа:
1
Ответ:
здесь два пути решения, покажу оба, а ты уже сам/а выбери,что будет более верным для твоей задачи.
Пошаговое объяснение:
с.
1)
-y(3y+4)
-y×3y-4y
-3y^2-4y
2)
-y(3y+4)
-y(3y+4)=0
y=0
y=-4/3
f.
1)
-3(y+7)
-3y×y-3y×7
-3y^2-21y
2)
-3(y+7)
-3y(y+7)=0
y=0
y=-7
i.
1)
-2y(-y-4)
-2y×(-y)-2y×(-4)
2y^2+8y
2)
-2y(-y-4)
-2y(-y-4)=0
y=0
y=-4
Похожие вопросы
Предмет: Қазақ тiлi,
автор: aiganymmustafa100709
Предмет: Қазақ тiлi,
автор: KUSAINCHIK
Предмет: Биология,
автор: alisarostovska13
Предмет: Литература,
автор: larisazurbina40
Предмет: Геометрия,
автор: evauseinova7